Creatividad y cognición musical: un acercamiento al aprendizaje de la composición (2015)
The present investigation is oriented towards obtaining the answer to the following question: which creative cognitive processes operate in the exercise of musical composition? Its general objective is to carry out the characterization of the processes of common use that emerge during the creative solution of problems (categorical reduction, search for attributes, mental mixing, conceptual interpretation, etc.). A multiple case study was carried out that directly observes them in the exercise of the composition carried out by two subjects facing the same cognitive task: composing a piece for soprano, guitar and electronics, based on a specific alchemical process agreed with Priority for both. It is based on a research carried out in 2011 by the author, whose findings serve as input for the ongoing study, which seeks an approach to learning the composition that contributes to reflection on the academic training of composers.